Exploring Euphemisms as Taboo Avoidance Strategies in the Mabia Languages - Issah, S.; Abubakari, H.; Atintono, S.; Atibiri, S. (Language Matters, 2023)
This article investigates the use of euphemisms in mitigating prohibited expressions in three Mabia (Gur) languages: Dagbani, Farefare (also known as Gurenɛ) and Kusaal. In the daily interactions of the Mabia people, they avoid using certain expressions, which are unmentionable in most contexts. These include the expressions for snakes and snakebite, sexual intercourse and genitalia, and death. The mention of the explicit terms for these expressions is face-threatening in Mabia society and can incur various forms of negative social consequences. Thus, instead of using these taboo expressions, speakers employ euphemisms as taboo-avoidance strategies; these euphemistic expressions oil social cohesion and indicate speakers’ communicative competence. The data used in this study were mainly gathered from primary sources. However, we augmented some of the primary data of Dagbani with some secondary sources drawn from N. A. Salifu’s (2012) PhD thesis. We employ politeness theory and ethnography of communication as analytical lenses
Research Article
Keywords: Mabia languages; social cohesion; face-threatening acts; positive face